A correlation of clinical, hormonal and ultrasonography features of polycystic ovarian syndrome among adolescent and reproductive age group women attending OPD in Navodaya medical college - D., Rita; M. P., Geethanjali; Reddy, Kappu Shanthi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Polycystic ovarian syndrome is the most common complex endocrine disorder in women of reproductive age. It is characterized by an array of clinical, endocrinal and metabolic manifestation. Aim of this study was to examine the correlation between clinical, hormonal and ultrasonography features in women diagnosed as polycystic ovarian syndrome. Methods: A cross sectional study of 100 reproductive age group women who had irregular cycles and polycystic ovarian morphology on ultrasound. Data about the menstrual history and anthropometric measurements were collected. Clinical observations were like hirsuitism and acanthosis nigricans was noted. Results: In all 100 PCOS women were studied and analysed. The mean age was 24.27(±5.64), mean BMI was 26(±4.8). Among the PCOS women 82% had oligo menorrhoea, 38% had hirsuitism and LH:FSH ratio deranged in 37% cases. The association between women having oligomenorrhoea and obesity with PCO morphology on scan was statistically significant. Conclusions: Young women who are diagnosed as dysregulated PCO are at a high risk to develop PCOD and long term sequel such as diabetes, hypertension and infertility. Lifestyle modification is advisable for managing symptoms and preventing long term complications and have a quality life.